Literature Review: Identifikasi Bakteri Salmonella sp pada Telur yang Dijual di Pasar Tradisional - Egi Apriyanto (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Eggs are animal products that serve as one of the main sources of animal protein containing essential nutrients beneficial for human health. They are widely consumed due to their affordability, high nutritional value, and ease of processing. However, eggs are also one of the most common media for the contamination and transmission of Salmonella sp., a bacterium that causes Salmonellosis, which can infect poultry, mammals, and humans. This study aims to determine the contamination level of Salmonella sp. bacteria in eggs sold in traditional markets. The research method used is a literature review with a qualitative descriptive approach by collecting, synthesizing, and analyzing data related to the Salmonella Shigella Agar (SSA) test. The study results show that Salmonella sp. contamination was highest in quail egg samples at 43.75%, followed by native chicken eggs (33.4%) and broiler eggs (33.33%). These findings indicate that eggs sold in traditional markets are susceptible to Salmonella contamination, which poses a potential risk to food safety and public health. Therefore, it is essential to strengthen handling, sanitation, and storage practices during production and distribution to reduce microbial contamination and ensure consumer safety.